2019
DOI: 10.1016/j.neuroimage.2019.06.059
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral preview effect with faces: Combined EEG and eye-tracking suggests multiple stages of trans-saccadic predictive and non-predictive processing

Abstract: The peripheral preview effect with faces: Combined EEG and eye-tracking suggests multiple stages of trans-saccadic predictive and non-predictive processing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 102 publications
7
38
3
Order By: Relevance
“…3 that can be due to a stronger prediction of the upcoming stimulus and therefore a stronger phantom percept. Our results are in agreement with recent studies demonstrating the existence of a partial but systematic transsaccadic integration of visual features across saccades 15 17 , 19 , 26 , 42 as well as the neural signature of the transsaccadic memory 43 , 44 .…”
Section: Discussionsupporting
confidence: 93%
“…3 that can be due to a stronger prediction of the upcoming stimulus and therefore a stronger phantom percept. Our results are in agreement with recent studies demonstrating the existence of a partial but systematic transsaccadic integration of visual features across saccades 15 17 , 19 , 26 , 42 as well as the neural signature of the transsaccadic memory 43 , 44 .…”
Section: Discussionsupporting
confidence: 93%
“…The FRP N170 effect was of slightly smaller amplitude and longer latency than that of the ERP effect. The longer latency is consistent with the result of a very recent study using face stimuli with FRPs, although that study did not address the face-effect per se as no non-face stimuli were presented (Huber-Huber et al, 2019). In addition, there was no direct comparison to ERPs (ERPs in that study were limited to peripheral stimuli and showed even later N1).…”
Section: Discussionsupporting
confidence: 80%
“…While the ERP and FRP differential face-effect showed overall similar components and topographies viewing there are changes across of the whole visual field following the eye movement. Second, since the saccade is self-generated (even if cued), free viewing may not only utilize peripheral information to predict the input (Huber-Huber et al, 2019), but also generate precise temporal predictions. These differences might affect components associated with both high and low-level feature processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiology studies with monkey subjects showed latencies in this order (30-50 ms) to spatial frequencies in the superior colliculus (Mazer et al, 2002;Chen et al, 2018a). This rapid postsaccadic response would allow for the read-out of visual information significantly earlier than expected based on previous trans-saccadic studies measuring high-level visual information about object identity or category, which showed time scales well over 100 ms (Edwards et al, 2018;Huber-Huber et al, 2019). High-level visual information, such as facial identity, is represented by neurons with large receptive fields and requires more time to process than SF.…”
Section: Discussionmentioning
confidence: 59%